Advancement in ceramic biomaterials for dental implants - Upadhyay A.; Pradhan L.; Yenurkar D.; Kumar K.; Mukherjee S. (My University, 2025)
There has been enormous research on diagnostic and therapeutic dental methods due to the growing recognition of oral wellness. Numerous studies in this area have resulted in dental biomaterials, including polymers, metals, and acrylic resins, essential to restore teeth affected by illnesses or accidents. Compared to other biomaterials, such as metals or polymers, ceramics offer distinct features. Materials like zirconia and alumina demonstrate their high intrinsic strength, making them appropriate for biomedical applications like dental implants or artificial joints. Additionally, they have outstanding biocompatibility, which lowers the possibility of adverse effects or inflammation. Some ceramics, like hydroxyapatite (HA) and bioactive glasses, even encourage tissue integration and regeneration. Moreover, because of their adaptability, they can be precisely shaped and composed to emphasize specific characteristics. Yttria-stabilized tetragonal zirconia offers outstanding mechanical properties and biocompatibility but faces concerns over long-term durability due to low-temperature degradation. To address this, researchers have developed non-oxidic ceramics like silicon nitride and advanced oxide-based materials like alumina-zirconia composites, aiming to enhance the durability and reliability of biomedical applications. In this review, we highlighted the recent advancements in ceramic dental implants; examples and applications of different ceramics-based materials, including zirconia, alumina, HA, and beta calcium phosphate, are provided in detail. © 2024, John Wiley and Sons Inc. All rights reserved.